1998
DOI: 10.1152/ajpgi.1998.274.4.g734
|View full text |Cite
|
Sign up to set email alerts
|

Telenzepine-sensitive muscarinic receptors on rat pancreatic acinar cells

Abstract: . Telenzepinesensitive muscarinic receptors on rat pancreatic acinar cells. Am. J. Physiol. 274 (Gastrointest. Liver Physiol. 37): G734-G741, 1998.-To identify the muscarinic subtype present on the rat pancreatic acinar cell, we examined the effects of different muscarinic receptor antagonists on amylase secretion and proteolytic zymogen processing in isolated rat pancreatic acini. Maximal zymogen processing required a concentration of carbachol 10-to 100-fold greater (10 Ϫ3 M) than that required for maximal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 24 publications
2
28
1
Order By: Relevance
“…However, in the present study we provide unambiguous evidence that cholinergic activation of pancreatic digestive enzyme (amylase) secretion is mediated by a mixture of M 1 and M 3 mAChRs, at least in the mouse. Several years ago, Schmid et al (1998) reported that the M 1 receptor-preferring antagonist telenzepine (a pirenzepine analog) was about 1000 times more potent than 4-DAMP in inhibiting carbachol-induced amylase secretion in rat pancreatic acini. However, 4-DAMP (Dörje et al, 1991;Caulfield and Birdsall, 1998) and telenzepine (Schudt et al, 1989;Lazareno et al, 1990;Karton et al, 1991) are known to bind to M 1 receptors with similar affinities (K i ϳ 1-3 nM), and even high concentrations of the classical M 1 receptor-preferring antagonist pirenzepine had no effect on carbachol-induced amylase secretion (Schmid et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study we provide unambiguous evidence that cholinergic activation of pancreatic digestive enzyme (amylase) secretion is mediated by a mixture of M 1 and M 3 mAChRs, at least in the mouse. Several years ago, Schmid et al (1998) reported that the M 1 receptor-preferring antagonist telenzepine (a pirenzepine analog) was about 1000 times more potent than 4-DAMP in inhibiting carbachol-induced amylase secretion in rat pancreatic acini. However, 4-DAMP (Dörje et al, 1991;Caulfield and Birdsall, 1998) and telenzepine (Schudt et al, 1989;Lazareno et al, 1990;Karton et al, 1991) are known to bind to M 1 receptors with similar affinities (K i ϳ 1-3 nM), and even high concentrations of the classical M 1 receptor-preferring antagonist pirenzepine had no effect on carbachol-induced amylase secretion (Schmid et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent RT-PCR studies have shown that rat pancreatic acini not only express M 3 but also M 1 mAChR mRNA (Schmid et al, 1998;Turner et al, 2001). To examine whether both acinar M 1 and M 3 receptors play a role in cholinergic stimulation of exocrine pancreas secretion, we used M 1 Fisahn et al, 2002) and M 3 receptor single KO mice ) and recently generated M 1 /M 3 receptor double KO mice as novel experimental tools.…”
mentioning
confidence: 99%
“…Physiologic agonist stimulation is associated with maximal enzyme secretion and minimal zymogen activation; supraphysiologic stimulation reduces secretion and causes pathologic zymogen activation (38). Inhibiting RYR Ca 2ϩ release during physiologic stimulation has been shown to diminish the basolateral component of the Ca 2ϩ wave but does not affect its capacity to elicit maximal enzyme secretion (36).…”
Section: Table 1 Caerulein Responses In Acinar Cellsmentioning
confidence: 99%
“…For example, previous studies have indicated coexpression of M 1 and M 3 receptors in rat striatum (36) and sublingual glands (7). Moreover, in rat pancreatic acinar cells that have receptors and signal transduction pathways very similar to those described for gastric chief cells (25), pharmacological and PCR analysis was consistent with the presence of both M 1 and M 3 receptors (33).…”
Section: Discussionmentioning
confidence: 60%
“…However, none of these studies excluded the possibility that chief cells coexpress M 1 and M 3 receptors. For example, pharmacological and PCR analysis of muscarinic receptor expression in dispersed acini from rat pancreas are consistent with expression of both M 1 and M 3 muscarinic receptors (33). It is of interest that the cellular biology of the gastric chief cell and pancreatic acinar cell is very similar (25).…”
mentioning
confidence: 88%